Peran Perpustakaan dalam Mendorong Inklusi Sosial: Studi Kasus pada Dinas Kearsipan dan Perpustakaan Kabupaten Semarang - Ambrosius Sindu; Anton Hermawan; Tintien Koerniawati (Universitas Islam Negeri Salatiga, 2025)
The purpose of this study is to outline how the Semarang Regency Archives and Library Office promotes social inclusion through initiatives that broaden access, boost community involvement, and cultivate empowerment. Data was gathered using a descriptive qualitative method that included document analysis, observations, and interviews. According to the findings, the library has evolved from a conventional book collection to an active supporter of social inclusion initiatives including ICT, cooking, sewing, and culturally-based activities. Although there are still restrictions on comfort, accessibility for people with disabilities, and resource sustainability, the facilities that are provided support a variety of activities. Roles as teachers, participants in the program, and proposers of future activities all demonstrate community involvement. Participation obstacles were also noted, including differences in availability and age and gender. Increased skills, economic independence, social solidarity, and community involvement in literacy and cultural development are just a few of the observable effects of the inclusion initiatives. In summary, the Semarang Regency Archives and Library Office is an important social change agent that empowers communities, promotes active participation, and facilitates access. However, more policy support, program diversity, and infrastructure improvements are still required.